2004
DOI: 10.1073/pnas.0405429101
|View full text |Cite
|
Sign up to set email alerts
|

Nodal protein processing and fibroblast growth factor 4 synergize to maintain a trophoblast stem cell microenvironment

Abstract: Before implantation in the uterus, mammalian embryos set aside trophoblast stem cells that are maintained in the extraembryonic ectoderm (ExE) during gastrulation to generate the fetal portion of the placenta. Their proliferation depends on diffusible signals from neighboring cells in the epiblast, including fibroblast growth factor 4 (Fgf4). Here, we show that Fgf4 expression is induced by the transforming growth factor ␤-related protein Nodal. Together with Fgf4, Nodal also acts directly on neighboring ExE t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
116
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(126 citation statements)
references
References 21 publications
9
116
1
Order By: Relevance
“…and inducing apoptosis in human trophoblast cells. 24,36 Based on these evidences, we proposed that NOMO1 might be functionally involved in trophoblast cell growth regulation by miR-675.…”
Section: Discussionmentioning
confidence: 99%
“…and inducing apoptosis in human trophoblast cells. 24,36 Based on these evidences, we proposed that NOMO1 might be functionally involved in trophoblast cell growth regulation by miR-675.…”
Section: Discussionmentioning
confidence: 99%
“…This signaling axis also plays a role in the maintenance of pluripotency in the epiblast and trophectoderm compartments [27,57]. During early mouse embryogenesis, Nodal exhibits a dynamic expression pattern that lasts until mid gestation.…”
Section: Function and Expression Of Cripto-1 And Nodal During Embryonmentioning
confidence: 99%
“…8 Nodal also acts on extraembryonic stem cells to inhibit precocious differentiation of trophoblast stem cells. 9 In the human placenta, expression of Nodal and ALK7 has previously been reported. 10 We demonstrated that Nodal, signaling through ALK7, inhibits trophoblast proliferation and induces apoptosis.…”
mentioning
confidence: 99%